The World a brief introduction - Haass, Richard (New York Penguin Press, 2020)
Like it or not, we live in a global era, in which what happens thousands of miles away has the ability to affect our lives. This time, it is a Coronavirus known as Covid-19, which originated in a Chinese city many had never heard of but has spread to the corners of the earth. Next time it could well be another infectious disease from somewhere else. Twenty years ago it was a group of terrorists trained in Afghanistan and armed with box-cutters who commandeered four airplanes and flew them into buildings (and in one case a field) and claimed nearly three thousand lives. Next time it could be terrorists who use a truck bomb or gain access to a weapon of mass destruction. In 2016 hackers in a nondescript office building in Russia traveled virtually in cyberspace to manipulate America's elections. Now they have burrowed into our political life. In recent years, severe hurricanes and large fires linked to climate change have ravaged parts of the earth; in the future we can anticipate even more serious natural disasters. In 2008, it was a global financial crisis caused by mortgage-backed securities in America, but one day it could well be a financial contagion originating in Europe, Asia, or Africa. This is the new normal of the 21st century.
Includes index
Keywords: World history